DATA PROCESSING SYSTEM MUTATIONS OF GOODS IN. METRO PACIFIC REALTY - Endriansyah Endriansyah; IRE Puspa W, SKom, MM IRE Puspa W, SKom, MM (Jurnal Sistem Informasi, 2001)
PT. Metro Pacific Realty is a company engaged in the field of entertainment. In its activities require operational items that supports these activities. Operational items should be stored somewhere or commonly called warehouses. However, in the warehouse inventory data processing system, especially on goods movement, there is still lack of making statements that were not quick enough, searching data, and recording transactions of goods are still done manually. Therefore the authors would like to improve the deficiency in the form of research writing with a "Goods Movement Data Processing System At PT. Metro Pacific Realty. "